Donor and recipient age matching in heart transplantation: analysis of the UNOS Registry. (8th August 2019) - Jawitz, Oliver K.; Raman, Vignesh; Klapper, Jacob; Hartwig, Matthew; Patel, Chetan B.; Milano, Carmelo
Summary: The association of donor and recipient age with survival following adult heart transplantation has not been well characterized. The purpose of this study was to examine the impact of the relationship between donor and recipient age on post‐transplant survival. We retrospectively reviewed the 2005–2018 UNOS heart transplant database for all adult recipients undergoing first‐time isolated heart transplantation. The impact of donor and recipient age on survival was analyzed with Cox proportional hazards modeling using restricted cubic splines. A total of 25 480 heart transplant donor and recipient pairs met inclusion criteria. Unadjusted and adjusted Cox proportional hazards modeling demonstrated a near‐linear association between increasing donor age and decreased survival; in addition, older and younger recipient age was associated with decreased survival. After adjustment, there was no significant interaction between donor and recipient age. Older donors decreased survival similarly in both older and younger recipients. Increasing donor age and both younger and older recipient age are independently associated with worsened post‐heart transplant survival. The relationship between donor and recipient age does not significantly affect survival following heart transplant.